RESPON FISIOLOGIS KAMBING BOERAWA JANTAN FASE PASCASAPIH DI DATARAN RENDAH DAN DATARAN TINGGI - Hadi Pramono; Sri Suharyati; Purnama Edy Santosa (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2014)
This research was carried out in October-December, 2012, the District of Gisting, Tanggamus Regency (upland) andin the Negri Sakti, Pesawaran Regency Settings Gedong Tataan (lowland). The methods used in this research is aSurvey method. Research Data were taken from 30 goats Boerawa pascasapih phase which includes males, rectaltemperature values, the frequency of heart rate, and respiratory frequency. Analyzed using t-test.The data collected from this research result indicates a very real (P<0.01 ) against temperature rektal, frequencyheart rate, and frequency respiration male goat boerawa phase pascasapih preserved in lowland (P1 ) and uplands (P2 ). Average value temperature rektal, frequency heart rate, and frequency respiration livestock, both boerawa malephase pascasapih in lowland is 39,330C, 84 time/minutes and 42 time/minutes and average value temperature rektal,frequency heart rate, and frequency respiration livestock, both boerawa male phase pascasapih on upland is 39,110C,74 time/minutes and 31 time/minutes.